Elasticities of residential electricity demand in China under increasing-block pricing constraint: New estimation using household survey data. (September 2021) - Jia, Jun-Jun; Guo, Jin; Wei, Chu
Abstract: China has implemented the residential increasing-block electricity pricing (IBEP) policy since the second half of 2012, which is considered the most effective economic instrument in improving residential energy efficiency. Price and income elasticity are two fundamental parameters to guide both scholars and policy-makers in assessing whether and to what extend Chinese households respond to the policy. However, it presents the challenge of simultaneous determination of marginal price and electricity consumption; further, it is less examined from an empirical perspective due to the absence of micro-level data. To fill this gap, this study estimates price and income elasticity by establishing two instrumental variables, based on a unique dataset from the Chinese Residential Energy Consumption Survey 2014. Results show that the residential demand for electricity is price inelastic and that electricity is an essential commodity for households in the short run. It also shows great urban-rural disparity and regional heterogeneity of household electricity consumption behavior regarding short-run income elasticity. The estimated parameters of short-run price and income elasticities provide a valuable reference for policy-making regarding both a nationwide uniform and a differential regional perspective. Highlights: Price and income elasticity of China's residential electricity demand is examined. A unique dataset of the Chinese Residential Energy Consumption Survey 2014 is used. Residential demand for electricity, an essential commodity, is price-inelastic. Regional heterogeneity and urban–rural disparity of consumption behavior exists. The estimated parameters provide a valuable reference for policy-making.